United Republic of Tanzania - Public Expenditure Review FY02 : Report on Fiscal Developments and Public Expenditure Management Issues - World Bank (Washington, DC, 2013)
This Public Expenditure Review (PER) examines the overall fiscal discipline, which after targeting, and achieving recurrent surpluses by FY99, the targets for FY01 were set to provide scope for financing of priority sector activities under the Poverty Reduction Strategy, and accommodate increased foreign inflows in the form of program grants. However, recurrent deficits in FY01, and, the target for FY02, delivered a recurrent deficit of 2.5 percent of GDP. Nonetheless, these deficits are within the sustainability thresholds indicated by recent analyses of fiscal, and debt sustainability, and remain compatible with continued macroeconomic stability. The report also looks at the introduction of cash flow planning, and the innovation introduced with the public finance act, to then analyze the government resources, and expenditures, which overall, expenditures on the key priority areas increased, exceeding the additional debt relief available through the enhanced Heavily Indebted Poor Countries (HIPC) Initiative. The report subsequently focuses on two main sources of fiscal risks, namely, on public enterprise debts and retrenchment costs associated with privatization; and, on extra-budgetary commitments related to procurement. Containment of fiscal risks, and further work should be extended to quantify, and validate parastatal debts covering other resources of fiscal risks, including commitments to privatization. Recommendations include a review of the existing tracking systems to identify information gaps, and recommend how systems can be streamlined, how information flows can be improved, and to clarify roles, and responsibilities of key institutions in this process. Moreover, attention should be paid to both financial reporting, and service delivery, including ways of integrating the two, in addition to identifying links to the poverty monitoring process.